Chapter Strangers in a Foreign Language - Dogramaci, Burcu (Studien aus dem Warburg-Haus, 2018)
Since the 19th century, art historians frequently faced the challenge of writing for an international audience and thus to translate their own work in another language. The book aims to study the biographical and academic impact of these self-translations, and how the adoption and processing of foreign-language texts and their corresponding methodologies have been fundamental to the disciplinary discourse of Art History.